Paylater Adoption as a Mediator Between Financial Literacy, Risk Perception, and Financial Behavior - Sujatmiko; Al Kausar (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
Technology-based financial services, such as paylater, are increasingly popular in Indonesia as a payment flexibility solution for consumers. However, the level of financial literacy and risk perception are key factors influencing the adoption of these services. This study aims to analyze the influence of financial literacy, risk perception, and paylater adoption on consumer financial behavior in Makassar using the Theory of Planned Behavior (TPB) approach. Data were collected through a survey of 100 respondents who had used paylater services for the past six months. The results showed that financial literacy had a significant influence on paylater adoption (coefficient 0.759; p < 0.001) and financial behavior (through mediation of paylater adoption). Paylater adoption also had a significant influence on financial behavior (coefficient 0.358; p = 0.026). Meanwhile, risk perception influenced paylater adoption (coefficient 0.181; p = 0.018), but did not directly influence financial behavior. This study emphasizes the importance of financial literacy in increasing consumer awareness of the risks and benefits of paylater services. These findings provide insights for financial service providers to improve consumer education to encourage responsible adoption.